How institutions shape land deals: The role of corruption - Matthias Bujko; Christian Fischer; Tim Krieger; Daniel Meierrieks (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2014)
Large-scale land acquisitions, or land grabs, concentrate in developing countries which are also known for their corruption-friendly setting caused by a weak institutional framework. We argue that corrupt elites exploit this given institutional set-up to strike deals with international investors at the expense of the local population. Using panel data for 157 countries from 2000-2011, we provide evidence that these land deals indeed occur more often in countries with higher levels of corruption.
Keywords: F21; O13; Q15; Q34; 330; large-scale land acquisitions; land grabbing; foreign investments; weak institutions; property rights; corruption; large-N study